PENDAMPINGAN IMPLEMENTASI MODERASI BERAGAMA DALAM PENGUATAN MANAJEMEN MADRASAH UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MAN 2 BOGOR: PENDAMPINGAN IMPLEMENTASI MODERASI BERAGAMA DALAM PENGUATAN MANAJEMEN MADRASAH UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MAN 2 BOGOR - Ima Rahmawati; Joko Trimulyo; Hana Lestari (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2026)
This community service project aims to analyze the effectiveness of mentoring based assistance in implementing religious moderation to strengthen madrasah management and improve educational quality at MAN 2 Bogor. The main issue is the limited integration of religious moderation values in governance practices that remain normative and unsystematic. The study applies a participatory and collaborative approach through mentoring stages including needs analysis, planning, implementation, monitoring and evaluation, and reflection. Results show a significant improvement in integrating religious moderation values into management functions including planning, organizing, actuating, and controlling. In addition, teachers and staff demonstrate improved understanding of moderation indicators such as tolerance, national commitment, anti radicalism, and accommodation of local culture. The mentoring process also fosters an inclusive, collaborative, and adaptive organizational culture. These findings confirm that participatory mentoring effectively strengthens madrasah management and improves educational quality.